Methodological and methodical aspects of consequenses of participation in war action - Domanskaitė-Gota, Vėjūnė (Genocidas ir rezistencija, 2002)
War is a very traumatic experience. The severity of its effect on those involved is various and the duration of the impact of this experience depends on many things – on individuals themselves, on people close to them, on society, and, hence, on all of us. We all know that some Lithuanian men have experienced the horrors of war, the horrors of the Afghan war. Do we know how they live, how they feel, how they have been affected by that experience? Do we care, or is it easier to take the position of see no evil, hear no evil? Studies have shown that one very important factor in overcoming traumas of the past is the social and political recognition of the trauma. Afghanistan war veterans and their experiences are shrouded in oblivion and secrecy. We hope that this study on the psychological effects of the Afghan war on its participants will help to pierce the veil of the Afghan war veterans’ experience and encourage further research.